Menangani Tantangan Sosial dan Ekonomi di Era Gen Z - Berwin Anggara; Annisa Fauziah Masfufah; Indah Permata Sari; Lintang Rahayu; Lukman Hakim; Mico Prastio; Olivia Yonata; Sindi Fatica Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
Generation Z, which includes individuals born between the mid-1990s and the early 2010s, faces various significant social and economic challenges in the modern context. This journal explores key issues faced by Gen Z, including mental health, education costs, job market uncertainty, and social isolation. Additionally, the research identifies the impact of social media and changing social values on their well-being. Through in-depth analysis, this journal proposes a series of mitigation strategies, such as enhancing financial education, improving access to mental health services, and providing skills training relevant to industry needs. By focusing on implementable solutions, this journal aims to offer valuable insights for educators, policymakers, and society in supporting Generation Z in navigating the complex challenges of the digital era.